Steroids for the Treatment of Misophonia and Misokinesia - Webb, Jadon; Williamson, Afton (Case Reports in Psychiatry, 2024)
Misophonia and misokinesia are disorders characterized by intensely negative physical and emotional reactions to specific auditory and visual stimuli. The availability of effective treatments, especially pharmacological ones, is limited. This report presents a case of a 35-year-old male with severe misophonia and misokinesia who experienced nearly complete resolution of symptoms while undergoing high-dose steroid therapy for an unrelated muscular injury. Two days after starting a 20 mg oral prednisone taper pack (in which the steroid dose is reduced by 4 mg daily), his Amsterdam Misophonia Scale (A-Miso-S) score drastically reduced from a baseline of 23 (i.e., extreme symptoms) to 1, with symptom relief persisting for approximately 2 weeks after completing the taper. Months later, a daily dose of prednisone (4 mg) was reintroduced. This again resulted in a marked reduction in symptoms (A-Miso-S of 6), enabling him to resume working in an office setting despite his triggers. Symptom improvement remained stable over several months. This case raises the possibility of the steroid prednisone as a novel treatment for misophonia and misokinesia. However, further investigation is needed to determine the generalizability of this observation.